Deciphering the changes in residential exposure to green spaces: The case of a rapidly urbanizing metropolitan region. (15th January 2021) - Zhang, Jinguang; Cheng, Yingyi; Li, Hongyi; Wan, Yi; Zhao, Bing
Abstract: Numerous studies have suggested that substantial residential exposure to green spaces (GSs) significantly impacts human health and quality of life. However, few studies have systematically assessed the spatial distribution of GS exposure and further deciphered the long-term changes in city-scale. Here we evaluated residential exposure to different types of GSs by incorporating three metrics: GS availability, estimated as the quantity of the overall surrounding greenness; accessibility, calculated using the minimum distance from residence to a GS; and attractiveness, evaluated by a modified gravity model integrating quality, travel time, and the number of potential visitors. Additionally, descriptive statistics were used to describe the changes in GS exposure over time. The changes in community-level GS exposure in Nanjing, China from 2008 to 2018 were analyzed and indicated that: 1) mean GS accessibility value increased by 15%, while availability and attractiveness decreased by 18% and 15%, respectively; 2) GS accessibility for 96.4% of the communities improved, while availability (mainly in the urban periphery) and attractiveness (mainly in the urban center) declined in 62.5% and 80.8% of the communities, respectively; and, 3) newly constructed communities were less likely to be exposed to GSs. Moreover, we emphasized that the increase in accessibility could not compensate for the loss of surrounding greenness according to the metrics that addressed different pathways associated with health benefits. Our findings provide a comprehensive understanding of the changes in residential exposure to GSs, affecting greening policies that address potential health issues caused by the lack of contact with GSs. Highlights: . Green Space (GS) availability, accessibility, and attractiveness were evaluated. Long-term, city-scale changes in residential exposure to GSs were analyzed. Gain in GS accessibility did not compensate for loss of surrounding greenery. Greening policies were proposed to improve residential exposure to GSs.